Feasibility Analysis and Marketing Channels for Etawa Crossbred Goat Farming Business in Banjaragung Village, Balongpanggang District, Gresik Regency - Fauzi, Ahmad; Laily, Dona Wahyuning; Fitriana, Nisa Hafi Idhoh (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
This study aims to determine the feasibility and marketing channels in the Etawa crossbred goat farming business in Banjaragung Village, Balongpanggang District, Gresik Regency. The population in this study was 16 Etawa crossbred goat farmers in Banjaragung Village. This study used business feasibility analysis, which included the calculation of the B/C Ratio, BEP unit, BEP price, BEP income, and the marketing margin analysis method to determine the efficiency level of the marketing channel. The result of the B/C Ratio calculation is 0,23, which means that the business is feasible to run because the result is more than 0. The result of the BEP unit calculation is 0,55 heads (1 head), the BEP price per head is Rp.2.317.214, and the BEP income is Rp.1.550.110, which means that the business is feasible to run because the average results obtained by farmers exceed the break-even point and the results of the calculation of the marketing margin analysis show that all farmers have a farmer share value above 50%, which means that all farmers have chosen an efficient marketing channel, namely marketing channel I (Farmers-Consumers) with a farmer share value of 100% and marketing channel II (Farmers-Blantik-Consumers) with a farmer share value of 90,34%.